2021
DOI: 10.3390/foods10102426
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Double Nanobody-Based Sandwich Immunoassay for the Detecting Staphylococcal Enterotoxin C in Dairy Products

Abstract: Staphylococcal enterotoxins (SEs) represent the leading reason for staphylococcal food poisoning (SFP) and various other diseases. Reports often indicate Staphylococcal enterotoxin C (SEC) as the most frequently found enterotoxin in dairy products. To minimize consumer exposure to SEC, this paper aimed to create a sandwich enzyme-linked immunosorbent assay (ELISA) based on nanobodies (sandwich Nbs-ELISA) to accurately detect SEC in dairy products without the influence of staphylococcal protein A (SpA). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This result suggests that these beads have a higher capture efficiency. To the best of our knowledge, there is no reported immunosensor using nanobodies against the E. coli strains, but similar results have been obtained with a sandwich immunoassay based on anti-staphylococcal enterotoxin C nanobodies for the detection of S. aureus in milk (LOD = 10 CFU/mL) [26,27]. Furthermore, our current assay showed satisfactory analytical performance compared to other recent conventional immunoplatforms used for the detection of pathogenic E. coli (Table 1).…”
Section: Performance Analysis Of the Immunoassaysupporting
confidence: 79%
“…This result suggests that these beads have a higher capture efficiency. To the best of our knowledge, there is no reported immunosensor using nanobodies against the E. coli strains, but similar results have been obtained with a sandwich immunoassay based on anti-staphylococcal enterotoxin C nanobodies for the detection of S. aureus in milk (LOD = 10 CFU/mL) [26,27]. Furthermore, our current assay showed satisfactory analytical performance compared to other recent conventional immunoplatforms used for the detection of pathogenic E. coli (Table 1).…”
Section: Performance Analysis Of the Immunoassaysupporting
confidence: 79%
“…This confirmed that the SERS aptasensor had good accuracy and could be used in practical applications. − In addition, the SERS aptasensor had the advantage of sensitive detection with a lower detection limit than that of the reported SEC detection methods (Table S2). ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…A significant breakthrough in botulism treatment involves coupling Nbs to poisoned botulinum toxin, enabling their delivery to nerve cells. This strategy has led to remarkable recovery in animals from botulism, showcasing the transformative potential of Nbs in disease treatment. , Expanding beyond the aforementioned bacteria, the development of Nbs against toxins produced by Staphylococcus aureus ,− and Listeria monocytogenes , has also shown promising progress. However, as of now, the in vivo neutralization effects of these Nbs remain untested.…”
Section: Progress Of Nbs Against Food-borne Biotoxins and The Neutral...mentioning
confidence: 99%